The Lord's Supper five views - Smith, Gordon T. 1953-; Gros, Jeffrey 1938- (Downers Grove, Ill. IVP Academic, 2008)
"Lord's Supper. Eucharist. Communion. Sacrament. Ordinance.While it's the meal that should unite us as followers of Christ, it sometimes appears we can't even agree on what to call it, let alone how we might share a common theological view of its significance. Even if we cannot reach full agreement, how can we better understand one another and this central observance of the Christian faith?
Introduction -- The Roman Catholic view / Jeffrey Gros. A Lutheran response ; A Reformed response ; A Baptist response ; A Pentecostal response -- The Lutheran view / John R. Stephenson ; A Roman Catholic response ; A Reformed response ; A Baptist response ; A Pentecostal response -- The Reformed view / Leanne Van Dyk. A Roman Catholic response ; A Lutheran response ; A Baptist response ; A Pentecostal response -- The Baptist view / Roger E. Olson. A Roman Catholic response ; A Lutheran response ; A Reformed response ; A Pentecostal response -- The Pentecostal view / Veli-Matti Kärkkäinen. A Roman Catholic response ; A Lutheran response ; A Reformed response ; A Baptist response
Introduction -- The Roman Catholic view / Jeffrey Gros. A Lutheran response ; A Reformed response ; A Baptist response ; A Pentecostal response -- The Lutheran view / John R. Stephenson ; A Roman Catholic response ; A Reformed response ; A Baptist response ; A Pentecostal response -- The Reformed view / Leanne Van Dyk. A Roman Catholic response ; A Lutheran response ; A Baptist response ; A Pentecostal response -- The Baptist view / Roger E. Olson. A Roman Catholic response ; A Lutheran response ; A Reformed response ; A Pentecostal response -- The Pentecostal view / Veli-Matti Kärkkäinen. A Roman Catholic response ; A Lutheran response ; A Reformed response ; A Baptist response.
Includes bibliographical references (p. [149]-154) and indexes
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Lord's Supper; Lord's Supper; Lord's Supper -- Roman Catholic Church; Lord's Supper -- Lutheran Church; Lord's Supper -- Reformed Church; Lord's Supper -- Baptists; Aufsatzsammlung